Perancangan Sistem Informasi Pengelolaan Kuesioner Pelatihan Pada PT Brainmatics Cipta Informatika - Karno Nur Cahyo; Martini Martini; Eri Riana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
Questionnaire is a technique of collecting data or information through forms that contain questions that will be filled in by several respondents to get responses or answers that will be analyzed by parties who have specific goals, besides the questionnaire is also one technique that is often used to make an assessment of item or service activities that are running. At present PT Brainmatics Cipta Informatika uses a questionnaire to assess the training that has been done, in practice at this time the questionnaire storage process is still ineffective and untidy, then the person in charge of training is often late or does not even report the results of the questionnaire when the training has been done, even though the results of the reporting are used to make improvements to the quality of the implementation of further training. Then from various divisions it was difficult to get the results of the questionnaire analysis needed by these divisions. Currently a web-based system application is needed that can carry out the process of managing the questionnaire as well as conducting automatic analysis of the questionnaire that has been filled out by the training participants, With this Information System for Managing Training Questionnaire, it is expected that the questionnaire data will remain well documented, and the results of the questionnaire analysis can be easily accessed by the training division, finance division and marketing division so that business processes related to each division can run more effectively and more efficiently